Gyrovirus: current status and challenge - Yan, Tianxing; Wang, Zhuoyuan; Li, Ruiqi; Zhang, Dabin; Song, Yuchen; Cheng, Ziqiang (Frontiers in Microbiology, 2024)
Gyrovirus (GyV) is small, single-stranded circular DNA viruses that has recently been assigned to the family Anelloviridae. In the last decade, many GyVs that have an apparent pan-tropism at the host level were identified by high-throughput sequencing (HTS) technology. As of now, they have achieved global distribution. Several species of GyVs have been demonstrated to be pathogenic to poultry, particularly chicken anemia virus (CAV), causing significant economic losses to the global poultry industry. Although GyVs are highly prevalent in various birds worldwide, their direct involvement in the etiology of specific diseases and the reasons for their ubiquity and host diversity are not fully understood. This review summarizes current knowledge about GyVs, with a major emphasis on their morphofunctional properties, epidemiological characteristics, genetic evolution, pathogenicity, and immunopathogenesis. Additionally, the association between GyVs and various diseases, as well as its potential impact on the poultry industry, have been discussed.Future prevention and control strategies have also been explored. These insights underscore the importance of conducting research to establish a virus culture system, optimize surveillance, and develop vaccines for GyVs.